2007
DOI: 10.1007/s10086-006-0881-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of modal-based damage-detection method to locate and evaluate damage in timber beams

Abstract: This paper employs modal-based damage detection algorithms to identify location of defects commonly found in timber and to estimate their severities. In this study, the authors propose modifications to an existing damage detection algorithm for locating and evaluating damage by comparing the modal strain energy before and after damage using the first two flexural modes of vibration. Experimental verification was performed on pin-pin supported timber beams by employing the algorithms with extracted modal parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 9 publications
(10 reference statements)
0
20
0
Order By: Relevance
“…Modal-based damage detection algorithm for identifying the location and extent of the defects in timbers was the subject of a recent study that came up with some modifications to the existing defect detection algorithms. In this study, researchers used the two initial modes of vibration to compare the modal strain energy before and after damage (Choi et al, 2007). In order to compare the mode shapes of vibration before and after damage in timbers, modal-based testing was applied on wood bars in order to propose a new statistical algorithm for obtaining a defect indicator .…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…Modal-based damage detection algorithm for identifying the location and extent of the defects in timbers was the subject of a recent study that came up with some modifications to the existing defect detection algorithms. In this study, researchers used the two initial modes of vibration to compare the modal strain energy before and after damage (Choi et al, 2007). In order to compare the mode shapes of vibration before and after damage in timbers, modal-based testing was applied on wood bars in order to propose a new statistical algorithm for obtaining a defect indicator .…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…1. Fig.1 illustrates that the first three modes of wood specimens are discrete, thus it is feasible to identify the intrinsic frequency by using single modal method [5,6].…”
Section: ) Identification For Intrinsic Frequenciesmentioning
confidence: 99%
“…Peterson et al [ 9 , 10 ] and Hu et al [ 11 ] developed statistical algorithms and damage indices by computing the mode shapes of timber beams before and after damage under vibration tests. Subsequently, Choi et al [ 12 ] proposed an improved damage detection algorithm to estimate the status of wooden material by comparing the modal strain energy derived from the first two flexural vibration modes. Similarly, the wavelet transform method [ 13 ], the transfer function method [ 14 , 15 ], and the mode shape reconstruction technique [ 16 ] were adopted to find the model shapes of timber, which revealed that the mode shapes before and after damage could be further utilized to identify the damage status and location in timber.…”
Section: Introductionmentioning
confidence: 99%